Cover Picture: Luminescence and Light‐Driven Energy and Electron Transfer from an Exceptionally Long‐Lived Excited State of a Non‐Innocent Chromium(III) Complex (Angew. Chem. Int. Ed. 50/2019). Issue 50 (19th November 2019) - Treiling, Steffen; Wang, Cui; Förster, Christoph; Reichenauer, Florian; Kalmbach, Jens; Boden, Pit; Harris, Joe P.; Carrella, Luca M.; Rentschler, Eva; Resch‐Genger, Ute; Reber, Christian; Seitz, Michael; et al.
Abstract : Inversion symmetry increases the excited‐state lifetime of a molecular ruby at room temperature in fluid solution to 4.5 ms while the photoluminescence quantum yield remains as high as 8.2 %, as shown by K. Heinze and co‐workers in their Research Article on page 18075. The chromium(III) complex [Cr(tpe)2 ] 3+ is furthermore competent in light‐induced electron and energy transfer processes, and thus resembles classical noble metal complexes.